Numerical simulation of green compacts - Hrairi, Meftah; Hussin, Asmu' (IIUM Press, 2011)
In the compaction process of metal powders into rigid dies, one of the most common problems is the part cracking during either the compaction stage or its ejection from die. Therefore, the finite simulation method is considered as design tool for powder metallurgy parts as well as for compaction tooling as this method allows the prediction of any kind of stresses and density distributions of the pressed compact prior to the actual tooling manufacturing activity. For this analysis, ANSYS LS-DYNA is used to facilitate the study of Geological Cap material model